2021
DOI: 10.1001/jamanetworkopen.2021.1728
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Extractability and Accuracy of Electronic Health Record Data for Joint Implant Registries

Abstract: IMPORTANCE Implant registries provide valuable information on the performance of implants in a real-world setting, yet they have traditionally been expensive to establish and maintain. Electronic health records (EHRs) are widely used and may include the information needed to generate clinically meaningful reports similar to a formal implant registry. OBJECTIVES To quantify the extractability and accuracy of registry-relevant data from the EHR and to assess the ability of these data to track trends in implant u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The accuracy of EHR data extraction has previously been shown for example, in joint implant registries. 43 The limitation of EHR extraction method is that physicians may make EHR entries in different ways, or some information may not be found in the EHR at all. This source of bias was minimized by extracting data of a random sample of patients over a long period of time, from different physicians, and from a long follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of EHR data extraction has previously been shown for example, in joint implant registries. 43 The limitation of EHR extraction method is that physicians may make EHR entries in different ways, or some information may not be found in the EHR at all. This source of bias was minimized by extracting data of a random sample of patients over a long period of time, from different physicians, and from a long follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…The data showed that extracting EHR data from the selected variables worked well in this type of study. The accuracy of EHR data extraction has previously been shown for example, in joint implant registries 43 . The limitation of EHR extraction method is that physicians may make EHR entries in different ways, or some information may not be found in the EHR at all.…”
Section: Discussionmentioning
confidence: 99%
“…A descriptive analysis of the main characteristics was performed: age, sex, length of stay, surgery act (replacement, repositioning, change, or reconstruction), surgery motif (arthrosis, fracture, cancer, infection, osteonecrosis or other main diagnosis) and device provided (head, stem, shell, or other) following Giori et al [6]. This descriptive analysis specifically specified the source of each of these data and missing data.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the classic manual constitution of a cohort is a long expensive process requiring a high workload for the teams. Moreover, a dynamic link between patients and outcomes could allow real-time updated surveillance [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…We completed a VHA pilot project to determine whether data in the VHA CDW are complete, accurate, and extractable enough to build a meaningful Level-I joint replacement registry 14 . By evaluating CDW data from 2000 to 2017, we found that the number of primary and revision total hip arthroplasties (THAs) performed in a VHA facility and recorded in the CDW increased steadily from 2000 to 2014, and then stabilized at about 4,000 to 4,500 per year.…”
Section: Use Of the Cdw To Develop A Vha Total Hip Arthroplasty Registrymentioning
confidence: 99%